Monoamine Oxidase and Other Mitochondrial Enzymes in Density Subpopulations of Human Platelets - Chamberlain, K G; Penington, D G (Thrombosis and Haemostasis, 1988)
Normal human platelets have been separated according to density on continuous Percoll gradients and the platelet distribution divided into five fractions containing approximately equal numbers of platelets. The mean volumes and protein contents of the platelets in each fraction were found to correlate positively with density while the protein concentration did not differ significantly between the fractions. Four mitochondrial enzymes (monoamine oxidase, glutamate dehydrogenase, cytochrome oxidase and NADP-dependent isocitrate dehydrogenase) were assayed and their activities per unit volume were found to increase in a very similar monotonie fashion with platelet density. When MAO and GDH were assayed on the same set of density fractions the correlation between the two activities was very high (r = 0.94–1.00, p <0.001) and a similar close correlation was found between MAO and ICDH. The results support the hypothesis that high density platelets either have a higher concentration of mitochondria or have larger mitochondria than low density platelets.
Keywords: Platelet density; Platelet monoamine oxidase; Platelet mitochondria; Platelet NADP-dependent isocitrate dehydrogenase